CDK digital marketing : addressing channel conflict with data analytics - Zettelmeyer, Florian, (SAGE knowledge. Cases., 2016)
Four years into a five-year contract with General Motors to be the exclusive website vendor to its U.S. network of more than 4,000 dealers, CDK Digital faced a crucial contract renewal at the end of 2012. The case follows Melissa McCann, director of strategic marketing, and Chris Reed, CMO, as they prepared for a critical meeting in July 2011: a presentation to the customer relationship management (CRM) subcommittee of the Chevrolet dealer council.